Factors Associated With Job Fatigue In Outpatient Nurses In Hospital X - Eviarista, Alfiana; Handayani, Putri (Sahabat Publikasi, 2024)
Work fatigue is a prevalent issue among public service workers, particularly nurses, impacting their performance and patient care. This study focuses on outpatient nurses at Hospital X in South Jakarta, aiming to identify factors associated with job fatigue. Using a quantitative cross-sectional design, data was collected from 100 outpatient nurses in 2023. Univariate and bivariate analyses, including the chi-square test, were conducted. Results revealed that 68.9% of nurses reported moderate fatigue, with significant associations found between high fatigue complaints and workload (p-value 0.000) and age (p-value 0.026). These findings underscore the need for Hospital X to address workload issues by considering additional personnel to mitigate fatigue among nurses. Such measures can enhance service quality and potentially improve nurse well-being, thereby benefiting patient care. Furthermore, implications suggest the importance of empathy training and holistic awareness of biopsychosocial components in addressing nurse fatigue and improving patient outcomes.